EFEKTIVITAS PENAMBAHAN GREEN ADSORBENT DI SEQUENCING BATCH REACTOR UNTUK MENURUNKAN PARAMETER BOD, TSS, DAN WARNA PADA LIMBAH INDUSTRI BATIK - Novirina Hendrasarie; Andhika Pratama Andhika (EnviroUS, 2021)
Currently, the industry in the field of batik production is one that has the potential to be developed. In the process, the batik industry produces liquid waste that reaches 80% of the total amount of water required. The waste produced will be a problem for the environment. The waste generated from the batik industry will be a problem for the environment. Batik industrial wastewater treatment can be carried out by means of biological treatment because it can reduce the organic content in batik wastewater. One of the effective and efficient waste treatment technologies is Sequencing Batch Reactor (SBR). The operating principle is filling and interesting SBR(fillanddraw),which consists of five stages: charging(fill), the reaction(reaction), precipitation(settle),d isposal of treated water(decand) and sludge disposal (idle).This study aims to determine the performance of SBR with the addition of green adsorbent in reducing the BOD, TSS and color content of batik wastewater. SBR was operated with a hydraulic retention time (HRT) and varying waste concentrations, namely 36 and 48 hours respectively and waste concentrations of 50% and 100% with the addition of coconut shell activated carbon, bamboo charcoal, and zeolite. This research was conducted with a process pre-treatment, namely coagulation and flocculation which will optimize the batik industrial waste treatment process. The results of this study indicate that activated carbon can describe parameters according to quality standards, especially coconut shells, which can reduce COD by 98.27%.